2021
DOI: 10.3892/etm.2021.10776
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose control contributes to protein stability of Ski‑related novel protein N in a rat model of diabetes

Abstract: Ski-related novel protein N (SnoN) negatively regulates the transforming growth factor-β1 (TGF-β1)/Smads signaling pathway and is present at a low level during diabetic nephropathy (DN), but its underlying regulatory mechanism is currently unknown. The present study aimed to assess the effects of insulin-controlled blood glucose on renal SnoN expression and fibrosis in rats with diabetes mellitus (DM). Streptozotocin-induced DM rats were treated with insulin glargine (INS group) following successful model esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Arkadia targets the TGF‐β pathway by modulating the stability of SMAD7 and nuclear corepressor Ski‐related novel protein N (SnoN) (Chen et al, 2020). SnoN, another interesting protein, which antagonizes the TGF‐β signaling, is downregulated by UPS during hyperglycaemia‐induced DN (Liang et al, 2021). In a similar way many other E3 ligases like CRLs (Zhang, Guo, et al, 2021), Nedd4L (Wilson et al, 2019), Smad ubiquitin regulatory factors (Smurfs) (Peng et al, 2022), and Tripartite motif‐containing (TRIM) superfamily have been shown to play a significant role in diabetic kidney diseases (Akhouri et al, 2023).…”
Section: Ups In the Manifestation Of Diabetesmentioning
confidence: 99%
“…Arkadia targets the TGF‐β pathway by modulating the stability of SMAD7 and nuclear corepressor Ski‐related novel protein N (SnoN) (Chen et al, 2020). SnoN, another interesting protein, which antagonizes the TGF‐β signaling, is downregulated by UPS during hyperglycaemia‐induced DN (Liang et al, 2021). In a similar way many other E3 ligases like CRLs (Zhang, Guo, et al, 2021), Nedd4L (Wilson et al, 2019), Smad ubiquitin regulatory factors (Smurfs) (Peng et al, 2022), and Tripartite motif‐containing (TRIM) superfamily have been shown to play a significant role in diabetic kidney diseases (Akhouri et al, 2023).…”
Section: Ups In the Manifestation Of Diabetesmentioning
confidence: 99%